Telaah Hukum: Pemberdayaan Undang-Undang No. 12 Tahun 2022 dalam Pembuktian Kasus Kekerasan Seksual - Helend, Erlindha; Pransisto, Johamran; Darwis, Muhammad; Mardaya, Andi (Jurnal Litigasi Amsir, 2025)
This research aims to determine the position of testimony from the victim's witness in proving Sexual Violence Criminal Acts based on Law No. 12 of 2022 concerning Sexual Violence Criminal Acts, and to identify the qualifications of valid evidence in proving Sexual Violence Criminal Acts based on Law No. 12 of 2022 concerning Sexual Violence Criminal Acts. This study adopts a normative research type with a statutory approach. The research results indicate that the position of the victim's witness testimony in proving sexual violence criminal acts is outlined in Article 25 (paragraph 1). The qualifications of valid evidence in proving sexual violence criminal acts are also outlined in Article 24 (paragraph 1), as regulated in Law No. 12 of 2022 concerning Sexual Violence Criminal Acts.